Sustainable surgical resource initiative for Haiti: the SSRI-Haiti project. Issue 1 (31st December 2023) - Frechette, Richard; Colas, Nathalie; Augustin, Marc; Edema, Nathalie; Pyram, Gerson; Louis, Stanley; Crevecoeur, Carl Eric; Mathurin, Carmeline; Louigne, Raphael; Patel, Bhavesh; Humphreys, Mitchell; Chapital, Alyssa; et al.
ABSTRACT: In response to the 2010 earthquake and subsequent cholera epidemic, St Luke's Medical Center was established in Port-au-Prince, Haiti. Here, we describe its inception and evolution to include an intensive care unit and two operating rooms, as well as the staffing, training and experiential learning activities, which helped St Luke's become a sustainable surgical resource. We describe a three-phase model for establishing a sustainable surgical centre in Haiti (build facility and acquire equipment; train staff and perform surgeries; provide continued education and expansion including regular specialist trips) and we report a progressive increase in the number and complexity of cases performed by all-Haitian staff from 2012 to 2022. The results are generalised in the context of the 'delay framework' to global health along with a discussion of the application of this three-phase model to resource-limited environments. We conclude with a brief description of the formation of a remote surgical centre in Port-Salut, an unforeseen benefit of local competence and independence. Establishing sustainable and collaborative surgery centres operated by local staff accelerates the ability of resource-limited countries to meet high surgical burdens.